THE IMPACT OF NEW PUBLIC MANAGEMENT ON PERFORMANCE-BASED BUDGET IN POLAND - Kościelecki Lech; Stańczyk Konrad (2020)
In a market economy, the state fulfilling its function (e.g. in administration, education, health and social security, public security, national defense, justice, etc.) has to bear certain expenses for their implementation. At the same time, the state does not directly produce any income which would provide it with any means to carry out these tasks. Hence, using the attribute of power, out of necessity, it has to refer to the income of other subjects from the private sector, thus making the redistribution of income. The primary source of state revenue are taxes. A taxpayer, forcibly charged by the state, is interested in the best use of his transferred funds. State’s performance should therefore be focused on ensuring the effectiveness of the management of collected public funds. Thus, the necessity for public administration is management based on respecting the principles of rationalization and the purpose of public expenditure, taking into account the liability (for specific performance), while guaranteeing the legality of the actions taken. Such conditions require not only a good measurement of the results, but above all, clearly defined aims and well-defined resources necessary to achieve them. The purpose of this article is to present the transformation of Polish public finance sector initiated by the Polish accession to the European Union and the need to implement the mechanisms resistant to the effects of economic crises to public sector.